ʺA competency model as a tool for improving the quality of vocational training in the educational and professional Master’s degree program "Social Institution Managementʺ. - Luniachek, V.; Ruban, N.; Kulyk, T. (Problems of Engineer-Pedagogical Education, 2021)
The paper presents a competency model as a tool to improve the quality of vocational training of graduates in the educational and vocational Master’s program "Social Institution Management” (specialty "Management"). Emphasis is placed on the fact that the development of the social sphere is an important component of the development of society as a whole. The analysis of the current state of vocational training of specialists for the social sphere in Master's degree programs at higher education institutions of Ukraine was carried out, which found that training is conducted in the following specialties: 231 "Social Work", 232 "Social Security", 028 "Management of Socio-Cultural Activities", 073 "Management". It was also determined that vocational training is carried out mainly under the educational program "Social Work" in fifteen institutions of higher education in Ukraine. Analysis of the content of education in specialty 231 "Social Work" and specialty 232 "Social Security" showed that they have similar content, but the emphasis is on the essence of social work. At the same time, the issues of social sphere management are ignored, as a result of which the quality of social services is reduced. Therefore, a competency model of the graduate in the specialty 073 "Management" in accordance with the educational program "Social Institution Management" was developed with regard to the established competency structure (knowledge, skills, and professionally important qualities). The list and names of competencies were taken from the approved standard of higher education in the relevant specialty. An example of a schematic consideration of the competency "Ability to implement scientific management methods in institutions and organizations of the social sphere" is given. The logical correspondence "competence – learning outcomes – discipline" in the specialty 073 "Management" in accordance with the educational program "Social Institution Management" is also substantiated. The presented learning outcomes also meet the approved standard of higher education in the relevant specialty. Based on the provisions of the theory of pedagogical assessment, it is proposed to use standard assessment methods to measure the individual components of each competency and integral competency as a whole. Approximate diagnostic methods are given. Vocational training under the educational vocational program "Social Institution Management" of the specialty 073 "Management" on the basis of the developed model will significantly improve the quality of educational services in the Master's program in this area.